The sources of output shocks in Finland and other EU countries - Helvi Kinnunen (Bank of Finland, 1998)
This paper examines the sources of output shocks in Finland as compared to other EU countries.The data consists of output fluctuations in main industries in nine current EU countries for the period 1978 - 1993.The sources of output shock are considered to consist of country-specific factors, sector-specific factors and a time factor, which is common to all countries and sectors. Fluctuation is partitioned using three-dimensional analysis of variance. Output shocks in Finland are clearly more country-specific than in other EU countries.A separate examination of the time period preceding the 1990s demonstrates that the result is not due to the exceptional recession in the beginning of the 1990s.The more central role that the country-specific factor has in Finland as compared to other EU countries is explained by the fact that average output growth was higher in Finland than in other EU countries until the end of the 1980s.Differences in growth rates between sectors also were larger than in other countries. Examination of the time period including the recession revealed that idiosyncratic economic cycle was clearly a more significant source of disturbances in Finland than in other countries. Examining the time period covering the depression also underlines the large volatility of the sheltered sector in Finland.
URN:NBN:fi:bof-20140807599
Keywords: 330; output shocks; output by industry; variance partitioning; EU countries